2015
DOI: 10.1182/blood-2014-11-613935
|View full text |Cite
|
Sign up to set email alerts
|

Variable content of von Willebrand factor mutant monomer drives the phenotypic variability in a family with von Willebrand disease

Abstract: Key Points VWD is characterized by variable expressivity, even within families with the same VWF mutation. The content of mutant monomers in the final multimeric structure may explain the observed variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…A DDAVP trial previously performed on a patient with a C1272S mutation reported by Penas et al in which platelet counts dropped from 200*10 9 L −1 to 157*10 9 L −1 at 30 min post-DDAVP treatment even though VWF:Ag, VWF:RCo, RIPA and presence of high molecular weight multimers were deficient relative to normal throughout the trial [15]. Relative to the patients reported here, DDAVP treatment of the C1272S patient only modestly reduced the platelet count indicating that perhaps the expression of the mutation was variable as has been observed with other type 2M/2A VWD patients with the same genotype within the same family [27]. Recombinant VWF studies using ristocetin induced platelet binding have previously indicated some gain- or loss-of-function dependency on which cysteine was mutated [11] and others have demonstrated that Cys->Ala mutations can abolish RIPA [12] indicating that ristocetin based assays are not functionally effective with mutations that alter the disulfide bonding of A1 in VWF.…”
Section: Resultsmentioning
confidence: 75%
“…A DDAVP trial previously performed on a patient with a C1272S mutation reported by Penas et al in which platelet counts dropped from 200*10 9 L −1 to 157*10 9 L −1 at 30 min post-DDAVP treatment even though VWF:Ag, VWF:RCo, RIPA and presence of high molecular weight multimers were deficient relative to normal throughout the trial [15]. Relative to the patients reported here, DDAVP treatment of the C1272S patient only modestly reduced the platelet count indicating that perhaps the expression of the mutation was variable as has been observed with other type 2M/2A VWD patients with the same genotype within the same family [27]. Recombinant VWF studies using ristocetin induced platelet binding have previously indicated some gain- or loss-of-function dependency on which cysteine was mutated [11] and others have demonstrated that Cys->Ala mutations can abolish RIPA [12] indicating that ristocetin based assays are not functionally effective with mutations that alter the disulfide bonding of A1 in VWF.…”
Section: Resultsmentioning
confidence: 75%
“…One possibility is that the low score observed in several members of the families reported here is due to a real lack of bleeding symptoms perhaps owing to a variable multimer structure (multimer information and data not available on all patients) with higher score achievers having a shift to low molecular weight multimers (LMWM) or loss of high molecular weight multimers (HMWM) which are crucial to hemostasis. In a recent study [25] of a 24 member pedigree with VWD type 2 and variable multimer distribution and bleeding, the variability was partially explained on the basis of mutant monomer incorporation in the final multimer structure of plasma VWF. In this family, different individuals carrying the same mutation could be classified as type 1, type 2A, or type 2M.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that altering the mutant incorporation into VWF multimers could be influencing the proper intracellular multimeric processing of VWF in the cases of R782Q, M771I, Y1146C and T1156M, as well as the function of the VWF multimer once it is secreted from the cell. We have recently shown that increasing the incorporation of a specific mutant VWF into larger VWF multimers may drive the pathogenesis of type 2 VWD; it is possible that a similar mechanism may occur in type 1 VWD (25). …”
Section: Discussionmentioning
confidence: 99%